2017
DOI: 10.1080/14670100.2017.1376423
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation under conscious sedation with local anesthesia; Safety, Efficacy, Costs, and Satisfaction

Abstract: Conscious sedation for cochlear implantation is a safe, efficient, and cost-effective alternative to general anesthesia. The efficacy of conscious sedation for cochlear implant surgery may expand the treatment of profound hearing loss to the elderly who are deemed too sick for general anesthesia or are fearful of the cognitive or medical consequences of general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Cochlear implantation is usually performed under general anesthesia without muscle relaxation to allow for facial nerve monitoring. Selected elderly patients have also been safely implanted under conscious sedation [13]. Patients should be preoperatively vaccinated according to Centers for Disease Control and Prevention (CDC) guidelines for meningitis prophylaxis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear implantation is usually performed under general anesthesia without muscle relaxation to allow for facial nerve monitoring. Selected elderly patients have also been safely implanted under conscious sedation [13]. Patients should be preoperatively vaccinated according to Centers for Disease Control and Prevention (CDC) guidelines for meningitis prophylaxis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can make "cooperative sedation," in which the patient remains arousable and cooperative without causing delirium and unnecessary movements associated with delirium [63]. CI under CS-LA achieved comparable results with general anesthesia (GA) regarding perioperative comorbidities and achieved better results than GA regarding patient satisfaction in elderly patient [63].…”
Section: Advances Of the Anesthetic Techniques 41 CI Under Consciousmentioning
confidence: 99%
“…Toner et al [58] reported a case series of cochlear implantation under local anesthesia; however, using local anesthesia in CI was not widely used till the last 10 years [59][60][61][62][63], especially after the introduction and widespread usage of dexmedetomidine as a sedative drug for cases of CS-LA. Dexmedetomidine can make "cooperative sedation," in which the patient remains arousable and cooperative without causing delirium and unnecessary movements associated with delirium [63]. CI under CS-LA achieved comparable results with general anesthesia (GA) regarding perioperative comorbidities and achieved better results than GA regarding patient satisfaction in elderly patient [63].…”
Section: Advances Of the Anesthetic Techniques 41 CI Under Consciousmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected elderly patients have also been safely implanted under conscious sedation. 18 Patients should be preoperatively vaccinated according to Centers for Disease Control and Prevention (CDC) guidelines for meningitis prophylaxis. 19 A 3 to 4 cm postauricular skin incision is designed to provide adequate exposure to the mastoid and place the receiver-stimulator device.…”
Section: Operative Techniquementioning
confidence: 99%